Lacework or mirror? : Diary poetics of Frances Burney, Dorothy Wordsworth and Mary Shelley /: Diary poetics of Frances Burney, Dorothy Wordsworth and Mary Shelley. (2013) - Ożarska, Magdalena
No abstract available